2013
DOI: 10.1002/eat.22086
|View full text |Cite
|
Sign up to set email alerts
|

Executive function in eating disorders: The role of state anxiety

Abstract: Objective: We examined the influence of depression and anxiety on executive function in individuals with a DSM-IV diagnosis of anorexia nervosa-restricting type, anorexia nervosa-binge-eating/ purging type, bulimia nervosa, or eating disorder not otherwise specified. Method:We assessed 106 women after their inpatient treatment in an eating disorders program. All participants were nutritionally stable at the time of testing.Results: Thirty percent of the total sample showed impaired performance on one or more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
(50 reference statements)
4
26
1
1
Order By: Relevance
“…No previous studies have investigated the effect of depressive symptoms on cognitive function in EDs using such a large neuropsychological battery. However, in a recent study, Billingsley‐Marshall et al found no significant effect of depression on variance in executive functioning. This aforementioned study included a larger number of patients with AN but only 13 patients with BN, which could possibly explain the different results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…No previous studies have investigated the effect of depressive symptoms on cognitive function in EDs using such a large neuropsychological battery. However, in a recent study, Billingsley‐Marshall et al found no significant effect of depression on variance in executive functioning. This aforementioned study included a larger number of patients with AN but only 13 patients with BN, which could possibly explain the different results.…”
Section: Discussionmentioning
confidence: 89%
“…Depression also negatively affects cognitive functioning in various domains . The present understanding of the effect of such comorbid psychiatric disorders on cognitive function in EDs is incomplete . Although some researchers have failed to find any effect of depression as a confounding variable, others have found that depression plays an important role in ED‐associated neuropsychological difficulties …”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized a positive correlation between higher Facebook use and higher disordered eating and that Facebook use would cause momentary increases in body dissatisfaction, anxiety, and urges to exercise. We focused on state anxiety because of its robust association with eating disorders …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, greater activation in the VLPFC/insula may predict poorer response to cognitive treatment because symptoms of anxiety interfere with treatment processes by undermining learning, motivation, and therapeutic engagement. In support of this hypothesis, a recent study found that state anxiety accounts for executive function deficits in women with AN (79). However, in our study, we did not measure anxiety symptoms so we cannot test this hypothesis, and our post-hoc analyses showed that VLPFC/insula activation did not differ between patients with and without a comorbid anxiety disorder.…”
Section: Discussionmentioning
confidence: 83%